The Concept of Tawhid Education from the Perspective of Mbah Kyai Abdul Kalam in the Book At-Tadzkiroh - Cahyani, Rosnella Dwi; Ma'ruf, Ahmad (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
In the context of the current moral and spiritual crisis among Muslims, understanding of tawhid is often merely theoretical without being accompanied by complete practice in daily life. This indicates the weakness of the foundation of tawhid in education. This study aims to examine the concept of tawhid education in the perspective of the book At-Tadzkiroh by Mbah Kyai Abdul Kalam, as an effort to rediscover deep Islamic values. The method used is qualitative with a literature review approach, through textual and contextual analysis of the book's content. The results of the study indicate that Mbah Kyai Abdul Kalam emphasizes the importance of purifying faith from all forms of polytheism, gaining a deep understanding of Allah's attributes through rational and spiritual approaches, and practicing the values of tawhid in concrete social life. Tawhid education in At-Tadzkiroh is holistic, encompassing the strengthening of intellectual aspects, spiritual deepening, and moral formation. The implications of these findings are the need to integrate classical tawhid values into the contemporary Islamic education system, so that students not only understand tawhid conceptually but are also able to apply it in their attitudes, behavior, and social contributions amid the challenges of the times.